"Float like a butterfly, sting like a bee" * : giving voice to planning practitioners. (1st October 2016) - Tasan-Kok, Tuna; Bertolini, Luca; Oliveira e Costa, Sandra; Lothan, Hila; Carvalho, Higor; Desmet, Maarten; De Blust, Seppe; Devos, Tim; Kimyon, Deniz; Zoete, J. A.; Ahmad, Peter
Abstract :